Oral Health-Seeking Behavior During The COVID-19 Emergency Policy Period in Padang City, Indonesia - Sari, Desy Purnama (Poltekkes Kemenkes Palu, 2023)
The increase in positive cases of Coronavirus Disease (COVID-19) has encouraged the Indonesian government to take lockdown policies by implementing Large-Scale Social Restrictions (PSBB) and Emergency Community Activity Restrictions (PPKM), which affect the paralysis of the health sector, especially dentistry. All actions in dental practice are limited to emergency case handling only, and many dentists have closed during the pandemic. The purpose of this study was to determine the differences in oral health-seeking behavior during the first phase of the lockdown in Padang City, West Sumatra, Indonesia. A survey method with a cross-sectional design was done by involving 120 respondents who have dental pain history. The data was collected by a self-administered questionnaire via google-form then analyzed by computerization using the fisher test. The results showed that during the PSBB period, most of the people in Padang (85%) treated dental pain independently, and only 15% asked for caregiver aids, specifically, only 3.3% of respondents take professional service. Meanwhile, during the PPKM period, the utilization of healthcare has increased by around 56,7%, (especially 43.4% treated by dental professionals, and 43.3% of respondents did self-medication. Thus, there was a significant difference of finding dental pain treatment behavior during PSBB and PPKM in Padang City (p = 0.004). As a result, limitation search for managing oral problems during COVID-19 has encouraged society to take self-medication or non-professional caregivers, so it is highly recommended to consult with dental professionals in the course of the pandemic through teledentistry without face-to-face meetings.